Perfil da pobreza na Bahia e sua evoluç\~ao no período 2004-2009 - Pedro H. G. F. de Souza; Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper aims to describe recent changes in the characteristics and living conditions of four income groups - extremely poor, poor, vulnerable and non-poor - in the state of Bahia between 2004 and 2009. We investigate the size of each group; their distribution between urban and rural areas; the coverage and impacts of the Bolsa Família and BPC programs; educational attainment; labor market insertion; age structure; size and composition of families; gender and race of household heads; access to sanitation and durable consumer goods. The first major conclusion is that there was a marked reduction in poverty and extreme poverty in Bahia during this period, although at a slower pace than in the rest of the country. Second, it is clear that individuals and families with reasonably sturdy - even if informal - connections to the labor market have benefitted from recent economic growth and were lifted out of extreme poverty. However, extreme poverty was not eradicated because there remains a sizable group with remarkably precarious or even non-existent links to the labor market. For this group, the Bolsa Família program was the most effective tool to alleviate their intense deprivation.
Keywords: I32; 330